Effect of packaging materials and storage conditions on the physicochemical and chemical properties of ogi powder - Awoyale, W.; Maziya-Dixon, B.B.; Abebe, M. (2013)
The effects of packages, storage conditions and the length of storage on the physicochemical and chemical properties of ogi powder produced from yellow maize grain were investigated. Ogi was produced using the traditional method, dried at 55°C to a powder in a cabinet drier, milled, cooled and packed in high-density polyethylene bag (HDPE), a polypropylene woven sack (PP), and a polyvinyl chloride container (PVC). The samples were stored under different conditions for 12 weeks and sampled at three-week intervals for analysis. Significant differences were observed for all the physicochemical and chemical properties of the ogi powder investigated except for the water absorption capacity and the ash content. At the end of the storage period, PVC-packed ogi powder stored in the dark compartment of the storage box had the highest degree of yellowness (2632.33) and HDPE bag-packed ogi powder stored in the lighted compartment had the least one(2424.33). Ogi powder packed in PVC stored in the dark compartment had the highest final viscosity (193 RVU) and that packed in PP woven sack stored in the dark compartment had the lowest one(185 RVU). Ogi powder packed in PP woven sack stored in the lighted compartment had the highest setback (89 RVU) while that packed in PP woven sack and stored in the dark compartment had the lowest one (82 RVU). The overall mean of the sugar content at the end of the 12 weeks of storage was 1.14%; PP woven sack (2%) and PVC (0.59%) packed ogi powder stored in the lighted compartment of the storage box had the highest and lowest value, respectively. The overall mean of the starch content at the end of the 12 weeks storage period was 53.81%; ogi powder packed in PP woven sack and stored in the lighted compartment had the highest (66.1%) and ogi powder packed in PP woven sack stored in the dark compartment had the least (42.86%) value. After 12-weeks of storage, moisture content increased from 5.5% before storage to 10.23% in ogi powder packed in PP woven sacks and stored in the dark compartment. Therefore, HDPE bag could be used to store ogi powder at a temperature of 26.10-27.90°C and relative humidity range of 63-75% and ogi powder packed in PVC can be stored at a temperature and relative humidity range of 27.20-30°C and 58-66%, respectively, for good product quality.